To Study the Effects of Deep Neck Flexor Strengthening Exercises and Mckenzie Neck Exercises on Smart Phone Users Suffering From Neck Pain: A Comparative Study: Life Sciences-Physiotherapy - Buru Yana; Madhusmita Koch; Abhijit Kalita; Abhijit Dutta (International Journal of Life Science and Pharma Research, 2022)
Smartphone has become an integral part of our lives, they generally have a small screen because of which it is more likely to induce a slouched posture creating a line of sight mostly below eye level, formulating an improper posture when used for a prolonged period of time, for example, forward head posture (FHP) leading to neck pain. The purpose of the study is to compare the effectiveness of Deep neck flexor strengthening exercises with that of McKenzie neck extension exercises on smartphone users suffering from neck pain. It is a comparative experimental study. This study included (N=40) subjects with neck pain within the age group of 25-45 years. They arerandomly assigned into 2 groups (Group A and B). Group A had 20 (N=20) subjects who are treated with Deep neck flexor strengthening exercises, Group B had 20 (N=20) who are treated with McKenzie neck extension exercises. The subjects were given intervention 5 days a week for 6 weeks. For within-group analysis Paired sample t-test was used and to analyze between-group variables Independent sample t-test was done. Between DNF and McK groups no significant difference was found in NDI(p<1.18 ) and SFMPQ(p <1.17) while all outcome measures showed a significant difference in both DNF and McK groups(p=0.00)within the groups The results indicated that although both the treatment techniques, DNF and McK are effective in alleviating the neck pain in Smartphone users in terms of decreasing pain intensity and increasing functional ability as there was a significant difference within the two groups, but there was no significant difference between the DNF and McK group in decreasing pain intensity, increasing functional ability